A histomorphological assessment of endoscopic biopsies in patients with upper gastrointestinal diseases in a tertiary hospital setting in Nigeria - Charles NC; Ikhuoria OC; Olalekan KS; Kufre UU; McEinstein EU; Chibuike OI (Ibom Medical Journal)
This is a prospective, observational and descriptive study of all the upper gastrointestinal endoscopies (UGIE) that were performed between January 2020 and December 2022.